Relação entre o teste Lateral medicine ball throw e a força muscular de estabilizadores de quadril e coluna e cinemática do membro inferior: estudo transversal - Guirelli, Agnes Ramos (2021)
Introduction: The Lateral Medicine ball throw is a test that assesses throwing performance, involving the entire kinetic chain and the principle of force transfer during movement, which suggests an association between lower limb and trunk strength, as well as the kinematics of the lower limb, with the performance of this test. Objective: To verify the level of correlation between lower limb kinematic measures and hip and trunk muscle strength measures with performance on the Lateral Medicine ball throw. Methods: Cross-sectional study. Eighty-four healthy individuals (41 men and 43 women), aged 18 to 30 years, physically active, were evaluated. The assessment of maximum isometric strength was performed for the abductor, lateral rotator and hip extensor muscles of the dominant limb and for the flexor muscles; lateral flexors and trunk extensors. The 2D kinematic analysis of the hip, knee and ankle in the sagittal plane and of the knee in the frontal plane was performed during the countermovement phase of the Lateral Medicine ball throw test (3 kg), simultaneously with the quantification of the test performance (in meters). All tests were performed in 3 repetitions and the average was used for analysis. Pearson's Product-Moment Correlation test was used, considering a strong level of correlation for values between 0.5 ≤ r < 1 and p≤0.05, with α=5%. Results: Positive correlations from moderate (0.3 < r < 0.5) to high (0.5 < r < 1) were found between the strength of the lateral rotators, abductors and hip extensors, flexors and lateral trunk flexors with the performance of the test. There was a moderate positive correlation (r=-0.26) between knee abduction measures and test performance. Conclusion: Lower limb and trunk muscle strength are correlated with test performance. The position of the lower limb in the sagittal plane during the countermovement phase has no clinically relevant relationship with the test.